GRAINS INJURY AND DRYING MODES WHILE SEEDS PREPARATION - Дерев'янко, Д. А.; Сукманюк, О. М.; Дерев'янко, О. Д. (Podilian Bulletin: Agriculture, Engineering, Economics, 2017)
Some of the changes that are planned to introduce innovations in reducing grain trains and improving drying modes in the preparation of high-quality seeds in most cases does not reach the practical implementation due to reluctance to bear the risks of financial costs. The study is based on the rules and procedures contain appropriate methods that allow to unify the process of reducing injuries and improve drying modes while seed grains preparing. In the article the method of mathematical machines modeling, working elements and technological processes is used, the calculated differential equations, transformations and graphic determinations are based on the use of the mechanics laws and the processes of transportation and loading by screw, scraper, tape conveyors and other technical means are considered, which leads to grains trauma and their quality lowering. Optimal and proper drying conditions for seeds of different crops are established, which are the main factor in obtaining high quality seeds, especially of high energy and similarity. The article discusses the technological process of drying the seeds and shows the impact forces on the grains while moving along turns of the screw auger. Speed investigated the screw pressing seeds to the body and the angle of the spiral screw that affect the seeds injury. Experimental data on temperature conditions of drying for obtaining high quality seeds are proposed. The result of the proposed measures is concrete proposals for reducing the grains traumas, improving the drying modes, which will ultimately ensure the quality of seeds and the productivity of grain crops